(untitled) (Pakistan Journal of Engineering, Technology and Science, 2024)
The goal of our paper is to discuss a proposed event management system that focuses on providing customizable quality to the user through the use of an Android application that allow users to have more control over the details of their event. We will be using both primary and secondary data sources for our study, including observations, internet resources, press, and visual media. This application is an event management system that is a comprehensive tool that covers many of the key aspects of event planning and execution. By providing full control to the user with features such as the ability to create and delete events, assign tasks to participants, and collect quotation online without any hassle, it could help event organizers to manage events more efficiently and effectively and the proposed event management system using an android application could be user-friendly and accessible, allowing even those without extensive event planning experience to easily organize an event with just a few clicks. This could potentially make the process of organizing events more democratic and allow a wider range of individuals and organizations to plan and host successful events. The ability to monitor revenue collection and invite volunteers could also be useful in ensuring that events run smoothly and are successful. The fact that the application is implemented on a website and application, Is easy to access from anywhere could also make it convenient for both event organizers and participants to use. Overall, it seems like this event management application could be a valuable resource for anyone involved in planning and booking events.